Cancer Informatics 2023: Data Sharing and Federating Learning Point Towards New Collaborative Opportunities - Warner, Jeremy L.; Patt, Debra; Section Editors for the IMIA Yearbook Section on Cancer Informatics (Yearbook of Medical Informatics, 2023)
Objective: To summarize significant research contributions on cancer informatics published in 2022.Methods: An extensive search using PubMed/MEDLINE was conducted to identify the scientific contributions published in 2022 that address topics in cancer informatics. The selection process comprised three steps: (i) ten candidate best papers were first selected by the two section editors, (ii) external reviewers from internationally renowned research teams reviewed each candidate best paper, and (iii) the final selection of three best papers was conducted by the editorial board of the Yearbook.Results: The three selected best papers demonstrate advances in federated learning, drug synergy prediction, and utilization of clinical note data.Conclusion: Cancer informatics continues to mature as a subfield of biomedical informatics. Applications of informatics methods to data sharing and federated approaches are especially notable in 2022.
Keywords: Neoplasms; informatics; health information technology; disparities